Nano Zinc Oxide Green-Synthesized from Plumbago auriculata Lam. Alcoholic Extract - Mina Michael Melk; Seham S. El-Hawary; Farouk Rasmy Melek; Dalia Osama Saleh; Omar M. Ali; Mohamed A. El Raey; Nabil Mohamed Selim (Plants, 2021)
Zinc oxide nanoparticles (ZnO NPs) were synthesized by using an alcoholic extract of the flowering aerial parts of Plumbago auriculata Lam. Dynamic Light Scattering (DLS) revealed that the average size of synthesized ZnO NPs was 10.58 ± 3.350 nm and the zeta potential was −19.6 mV. Transmission electron microscopy (TEM) revealed that the particle size was in the range from 5.08 to 6.56 nm. X-ray diffraction (XRD) analysis verified the existence of pure hexagonal shaped crystals of ZnO nanoparticles with an average size of 35.34 nm in the sample, which is similar to the particle size analysis acquired by scanning electron microscopy (SEM) (38.29 ± 6.88 nm). HPLC analysis of the phenolic ingredients present in the plant extract showed that gallic acid, chlorogenic acid, and catechin were found as major compounds at concentrations of 1720.26, 1600.42, and 840.20 µg/g, respectively. Furthermore, the inhibitory effects of ZnO NPs and the plant extract against avian metapneumovirus (aMPV) subtype B were also investigated. This assessment revealed that the uncalcinated form of Nano-ZnO mediated by P. auriculata Lam. extract possessed a significant antiviral activity with 50% cytotoxic concentration (CC50) and 50% inhibition concentration (IC50) of 52.48 ± 1.57 and 42.67 ± 4.08 µg/mL, respectively, while the inhibition percentage (IP) was 99% and the selectivity index (SI) was 1.23.